A taxonomic revision of Rhamnus L. and Atadinus Raf. (Rhamnaceae) in Iran - Alijanpoor, Behnaz; Khodayari, Hamed; Assadi, Mostafa; Rahiminejad, Mohammadreza; Mehregan, Iraj (Phytotaxa, 2021)
This study aims to revise the taxonomic status of Rhamnus L. and Atadinus Raf. (Rhamnaceae) for the Flora of Iran. Nine species, including 15 taxa are recognized, described and compared with their closely related taxa. These include one new species, R. rahiminejadii Alijanpoor & Assadi, one new subspecies, R. pallasii subsp. mazandaranica Alijanpoor & Assadi, and one hybrid species, R. ×mehreghanii Alijanpoor & Khodayari (R. persica Boiss. × R. kurdica Boiss. & Hohen.). In addition, a hybrid species i.e, ×R. spathulifolia Fisch. & C. A. Mey., is accepted as a distinct species, R. spathulifolia Fisch. & C. A. Mey. and R. cornifolia and R. cornifolia var. denudata, from sect. Rhamnustrum Rouy. are transfered to genus Atadinus Raf. as A. cornifolius (Boiss. & Hohen.) Alijanpoor and A. cornifolius var. denudatus (Bornm.) Alijanpoor.